Variability of spectral lines of extrasolar system HD189733 during a transit - Y. O. Shliakhetska; Yu. G. Kuznyetsova; A. P. Vidmachenko; V. N. Krushevska (Вісник Астрономічної школи, 2014)
The results of processing and analysis of spectral observations of exoplanet system HD189733 are presented in the paper. The system consists of spectral type K1–K2 star and one extrasolar planet transiting across the star disk. Four object spectra were obtained with spectral resolution R=45000. High resolution coude-echelle spectrograph locating on the 2-meter mirror telescope Zeiss-2000 at the peak Terskol Observatory was used. It was detected increasing of depth and equivalent width of absorbing lines Hα, Hβ, Hγ, Hδ, H & K CaII, Na I D2 & D1 in spectra obtaining during transit and directly after that as compared with spectra obtaining during 30 minutes immediately before transit. Central emissions in H & K CaII lines were detected in all obtaining spectra.